Implementasi Pendidikan Inklusif di Masyarakat - Tintin Handiyati; Sulis Tyaningsih; Cecep Hilman (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2023)
Inclusive education as an approach to meeting the educational and learning needs of all children, youth and adults that focuses specifically on those who are disabled, marginalized and neglected. But with various problems, especially in implementation in society. Inclusive education that is currently running has not been realized optimally. The community also does not understand the paradigm of inclusive education so they cannot participate in it. The law states that the community is obliged to provide resource support in the implementation of education. Community participation and independence determine the implementation of this inclusive school policy. In Friendly Schools all school communities understand that the goal of education is the same for all, that is all students have the right to feel safe and comfortable, to develop themselves, to make choices, to communicate, to be part of the community, to be able to live in world situations constantly changing, to deal with life's many transitions, and to make a valuable contribution. Several steps that can be taken to implement inclusive education in society include: 1). Building community awareness and education, 2) Formulating inclusive education policies, 3). Conduct training for teachers and educators, 4). Doing an inclusive teaching approach, 5). Provide facilities and accessibility, 6). Building collaboration with Parents and Community.